Module On Leadership, Management and Governance in Health Care -Zimbabwe - Misheck Dzichauya (JOURNAL OF POLITICAL SCIENCE AND LEADERSHIP RESEARCH, 2026)
The module on Leadership, Management and Governance in the Healthcare in Zimbabwe focused on major induction skills that managers and leaders in the Healthcare were registered to be deficient in their day-to-day operations. The needs analysis was carried out through a survey where among other skills, the need for updated skills in leadership, management and governance were singled out as required for all managers in the Healthcare in Zimbabwe. The purpose of the module is to guide trainers of trainers in the areas of leadership, management, and governance in the Healthcare in Zimbabwe. The module takes the position that transformational leadership is vagus to the effective management of the Healthcare in Zimbabwe.